RF BASED AUTOMATIC RAILWAY TRAFFIC CONTROL SYSTEM - Ms. Rohini Mahadeo Garud,; Prof. B.T. Salokhe, (International Journal of Innovations in Engineering Research and Technology, 2022)
With the amplified demand on railway services all over the globe as cheapest medium of transportation, overall railway infrastructure has been developing rapidly in the last two decades, including its communication system. In the past wired communications system were used for signaling and data communication in the railway industry. Radio wave systems become more reliable and cheaper; it becomes feasible to use ad-hoc radio communications as an additional layer of safety, for prevention of crashes between trains in a rail control system. This has led to the invention of new features for railway safety, high speed monitoring of railway conditions. Conventional methods of railroad maintenance and safety assurance are based on separate periodical inspections of track and equipment. These methods have many limitations like problems about signaling system caused by configuration, high construction cost, inefficiency about maintenance work, long downtime etc.[1]